Anatomy and physiology of the rumen - Membrive, Claudia Maria Bertan [UNESP] (Springer Nature, 2016)
Herbivores can be classified as monogastric or polygastric. Equine, rabbits and elephants represent monogastric herbivores. They have one stomach that does not offer appropriate conditions for fermentative digestion. In these species, the fermentation chambers, which keep a great amount of microorganisms, are represented by the cecum and colon, and both compartments are very developed.